Diagnostic Accuracy Of Spectral Doppler Ultrasound In Diagnosis Of Malignant Breast Lesions Taking Histopathology As Gold Standard - Tabassum, Mehwish; Waseem, Rabia; Niazi, Manal; Riaz, Zainab; Shakil, Hamna; Anam, Wajeeha (Journal of Rawalpindi Medical College, 2024)
Objective: To determine the diagnostic accuracy of Spectral Doppler Ultrasound in malignant breast lesions, taking histopathology as the gold standard. Place and Duration of Study: This study was conducted at the Department of Diagnostic Radiology, Pak Emirates Military Hospital, Rawalpindi. The study duration was 06 months from 10th June 2020 to 10th December 2020. Methods: The study design was Cross-sectional.Consecutive non-probability sampling technique was used for sample collection. A total of 165 women with breast lumps with a duration of lump >1 month and of any size and age 25-65 years were enrolled. Each patient was subject to spectral Doppler ultrasound using a high-resolution unit with a linear array probe centred at 7.5MHz. The findings were interpreted by a consultant radiologist for the presence or absence of malignant breast lesions. All patients underwent biopsy in the concerned ward and the histopathology report was compared with spectral Doppler USG findings. Results: Sensitivity, specificity, positive predictive value, negative predictive value and diagnostic accuracy of Spectral Doppler Ultrasound in diagnosing malignant breast lesions, taking histopathology as gold standard was 91.84%, 83.86%, 89.11%, 87.50% and 88.48% respectively. All spectral Doppler indices, including mean peak systolic velocity (PSV), resistive index (RI), and Pulsatility index (PI) were significantly higher in malignant tumours. The optimal cut-off points were PSV = 12.5 cm/s (sensitivity: 85%, specificity: 82%), RI = 0.68 (sensitivity = 92%, specificity = 85%), and PI = 0.93 (sensitivity = 91%, specificity = 88%). Conclusion: The use of Doppler Ultrasound is a feasible, safer and non-invasive modality and has high sensitivity and specificity in the diagnosis of malignant breast lesions.